O ensino mediado pela simulação realística: atendimento de intercorrências de saúde por professores da educação infantil - Castro, Gabriela Van Der Zwaan Broekman (2018)
INTRODUCTION: Commonly health intercurrences happen with children in the school causing fatal events or those that culminate in sequels throughout the child's life. In this sense, the teacher should be familiar with first aid techniques, in order to be able to develop skills, prevent unnecessary injuries/consequences, and provide assistance to the child until specialized health support arrive in the school institution. As a strategy for training early childhood education teachers on first aid, educational interventions in health education are satisfactory. In this context, realistic simulation is an effective teaching technology, where questions of reality are repeated, in guided and controlled experiences, and where decision-making is allowed to be potentialized. OBJECTIVES: To analyze Realist Simulation’s contributions about school-age-child health intercurrences management in the school environment, in the experience of the elementary school teacher. MATERIALS AND METHODS: It’s a qualitative study, with an evaluation design of simulated activity, as an educational practice that is based on the concepts of Experiential Learning Theory. The study was carried out in three public schools of early childhood education and elementary education I of a city in the interior of São Paulo. An educational intervention was carried out with 45 teachers, with simulated scenarios in the first aid in the children's school, before the management of cardiorespiratory arrest, airway obstruction, convulsive crisis, falling with cut and hemorrhage. For data collection, 4 simulated scenarios were used, replicated 16 times, 4 focus groups and 27 individual interviews. The analysis of the data was made through analysis of qualitative inductive content. All the ethical recommendations established in Resolution 466/12 of the National Health Council were followed. RESULTS/ DISCUSSION: The analysis allowed us to apprehend experiences that were grouped by similarity:1) Realistic simulation as an experiential learning resource; 2) Need for transformation of the teaching-learning process; 3) Accidents and health intercurrences with children: subjects for the school space; 4) (A) the 'super' teacher (r). The realistic simulation for the approach of teachers to the first aid theme is effective, as it promotes experiential learning and erupts with decontextualized teaching methods. It can be considered a teaching tool that allows the learner to sustain the knowledge throughout its life, by cognitive correlations with lived experiences. When the teacher participate in an educational intervention on first aid, can demonstrate that it is possible to reflect about the practice itself to be carried out, as well as validating the improvement of the decision making process. FINAL CONSIDERATIONS: The school environment is conducive to lifes’s risk. This study raises questions related to the professional, ethical and citizenship teacher’s role. Teacher’s professional qualification to attend health emergencies is still incipient and based on disconnected training of the work routine. Inquiries regarding the co-responsibility of the teacher over another assignment should be considered, as familiarization and approximation of first aid techniques as citizens is necessary, but not by exempting the government's responsibility to strengthen the school in the face of child safety and protection.